Conservative treatment of acute appendicitis - Coccolini, Federico; Fugazzola, Paola; Sartelli, Massimo; Cicuttin, Enrico; Sibilla, Maria Grazia; Leandro, Gioacchino; de' Angelis, Gian Luigi; Gaiani, Federica; Di Mario, Francesco; Tomasoni, Matteo; Catena, Fausto; Ansaloni, Luca (Acta Biomedica Atenei Parmensis, 2018)
Acute appendicitis has been considered by surgeons a progressive disease leading to perforation for more than 100 years. In the last decades the theories about this concept gained attention, especially in adults. However, appendectomy for acute appendicitis remains the most common urgent/emergent surgical procedure. At present, accumulating evidences are showing the changing in clinical practice towards the non-operative management of several cases of acute appendicitis either non-complicated or complicated. The present review aims to show the literature results regarding the non-operative management of acute appendicitis in non-complicated and in complicated cases.